Search for Toxoplasma gondii (Eucoccidiorida: Sarcocystidae) in wild rodents of the Yucatan Peninsula, Mexico - Torres-Castro, Marco (2022)
The aim of this study was to detect Toxoplasma gondii DNA in skeletal muscle and kidney samples collected from small wild rodents, captured in 10 locations in the Yucatan Peninsula, Mexico (Campeche, Quintana Roo and Yucatan states) in 2018-2019. In total, 127 rodents of seven species were captured. A fragment of skeletal muscle and kidney was taken from all of them for genomic DNA extraction. The identification of T. gondii was carried out by nested PCR directed to a fragment of the B1 gene of the parasite. The rodent species with the highest number of captured individuals was Heteromys gaumeri (n=39). The PCR did not identify T. gondii DNA in the organs evaluated.